2018
DOI: 10.1159/000490837
|View full text |Cite
|
Sign up to set email alerts
|

Uncaria rhynchophylla Ameliorates Parkinson’s Disease by Inhibiting HSP90 Expression: Insights from Quantitative Proteomics

Abstract: Background/Aims: Uncaria rhynchophylla, known as “Gou-teng”, is a traditional Chinese medicine (TCM) used to extinguish wind, clear heat, arrest convulsions, and pacify the liver. Although U. rhynchophylla has a long history of being often used to treat central nervous system (CNS) diseases, its efficacy and potential mechanism are still uncertain. This study investigated neuroprotective effect and the underlying mechanism of U. rhynchophylla extract (URE) in MPP+-induced SH-SY5Y cells and MPTP-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…is finding was supported by the study done by Pal and Kumar [185] that demonstrated that Uncaria rhynchophylla exhibited anti-Parkinson's activity in 6-OHDA rat model. In another model of Parkinson's disease, Uncaria rhynchophylla has been reported to increase cell viability, attenuate dopaminergic neuronal loss of substantia nigra and striatum, inhibit heat-shock protein 90 and apoptosis, and thereby induce autophagy through MAPKs and PI3K-serine/threonine protein kinase (Akt) pathways in MPP + -induced SH-SY5Y cells and MPTP-induced mouse model [186].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…is finding was supported by the study done by Pal and Kumar [185] that demonstrated that Uncaria rhynchophylla exhibited anti-Parkinson's activity in 6-OHDA rat model. In another model of Parkinson's disease, Uncaria rhynchophylla has been reported to increase cell viability, attenuate dopaminergic neuronal loss of substantia nigra and striatum, inhibit heat-shock protein 90 and apoptosis, and thereby induce autophagy through MAPKs and PI3K-serine/threonine protein kinase (Akt) pathways in MPP + -induced SH-SY5Y cells and MPTP-induced mouse model [186].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…Pharmacological studies show that Uncaria rhynchophylla has an antagonistic effect on Ca 2+ , which can block external Ca 2+ influx and release of internal Ca 2+ [4]. It has a strong inhibitory effect on the cardiovascular system and significantly reduces blood pressure; it has obvious nerve conduction block infiltration anesthesia and spinal canal anesthesia; it has a significant inhibitory effect on the synaptic transmission process of the central nervous system and has antiepileptic effects [5][6][7]. It can be used to treat hypertension, sedation, sleeping, and antispasmodic effects [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The two herbs were reported to have positive effect on PD [8, 9] and have been used for patients who have motor dysfunctions in East Asia countries. Furthermore, Uncaria rhynchophylla extract has shown neuroprotective effect in MPP + -induced SH-SY5Y cells and MPTP-induced mice by increasing cell viability and ameliorating behavioral impairment through dopamine and tyrosine hydroxylase (TH) expression elevation [10]. Anti-apoptotic and antioxidative aspects of Gastrodia elata Blume in MPP + -induced cytotoxicity dopaminergic cells were also suggested [11].…”
Section: Introductionmentioning
confidence: 99%